The Effect of Del Nido Cardioplegia on Myocardial Function in Different Cardiac Surgeries: an observational study - Ehab M. F. Ahmed, Tarek Mohamed Afifi, Ahmed Badawy Mohammed Esawy, Mohammad Abdelrahman Hussein (South Eastern European Journal of Public Health, 2025)
Background: Reducing the ischemia time is an essential strategy to reduce intra-operative myocardial injury and improve postoperative outcomes. Myocardial protection is an essential aspect of modern cardiac surgical procedures. Objective: To evaluate the effect of Del Nido cardioplegia on myocardial function in adult patients undergoing various cardiac surgeries, including coronary artery bypass grafting (CABG), valve surgeries, and combined procedures and determine whether Del Nido cardioplegia provides adequate myocardial protection and facilitates efficient recovery in a diverse patient population with multiple comorbidities. Methods: This prospective cohort study was conducted at tertiary care hospital at Prince Sultan Cardiac Center-Najran-KSA from January 2023 till July 2024 and performed on total 47 adult patients undergoing CABG, valve surgeries, and combined procedures with inclusion and exclusion criteria. Results: Mean age (years) was 51.3±10.0, majority were males ((74.5%). Operations were CABG only, valve only and both (68.1%, 8.5% and 23.4% respectively). Mean±SD of total bypass time (min) was 77.7±13.4. Cardioplegia delivery were antegrade and antegrade+ retrograde (17.0% and 83.0% respectively). Glucose (mg/dL) and lactate (mg/dL) increased from before the CPB (144.2±27.2 and 1.2±0.5 respectively) to after the termination of CPB (183.7±27.1 and 2.3±0.5 respectively). Mean±SD of Ventilation time (hr), ICU stay (days) and Hospital stay (days) was 9.7±2.7(hr), 4.2±1.1 (days) and 13.0±1.2(days) respectively. Conclusion: This study highlights the efficacy and safety of Del Nido cardioplegia in adult cardiac surgeries. Despite the relatively high prevalence of comorbidities and the complexity of the procedures, patients demonstrated favorable recovery outcomes, including manageable ICU and hospital stays. The rising glucose and lactate levels during surgery reflect the anticipated metabolic stress of cardiopulmonary bypass, but Del Nido cardioplegia appeared to mitigate the associated risks. The findings suggest that this cardioplegia strategy is a viable option for both CABG and valve surgeries, providing effective myocardial protection and contributing to smooth postoperative recovery.